Sweetness & Light. The Mysterious History of the Honey Bee - Ellis H. Hattie (London, Sceptre, 2005)
In Sweetness & Light, Hattie Ellis tells the story of this amazing insect and its mysterious world, and how bees have flown into our lives throughout history, inspiring writers, artists, architects and scientists. She describes the complex politics of the hive and how bees make flights equivalent to three circuits of the globe to produce a pound of honey, each bee yielding less than half a teaspoonful in its lifetime. We learn of bees' collective power and how cutting-edge medical research is harnessing the therapeutic properties of their honey, venom and propolis. Travelling from heather moorland to inner city, Hattie Ellis talks to beekeepers from New Zealand to New York about how honey is produced and used today. Her captivating narrative shows how the mysteries of bees and honey remain a talisman for all that is curious, fascinating, delightful and perilous about the natural world and our place within it.